ANALISIS PENGENDALIAN STATISTICAL PROSES CONTROL (SPC) DALAM MENINGKATKAN KUALITAS PRODUKSI DI PT.TIRTA INVESTAMA - Madinatul Munawaroh; mustaqim (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
The bottled drinking water (AMDK) industry is a sector that is growing rapidly along with the increasing public demand for clean and healthy water products and has long been known for its commitment to maintaining product quality. In an effort to maintain product quality, the company faces challenges in the form of high reject rates that include categories such as contaminated, cracked, leaked, unsuitable contents, and not tight capshil.To overcome these problems, the Statistical process Control (SPC) method is used as a tool to analyze and monitor the production process. SPC tools such as check sheets, Pareto diagrams, control charts, and fishbone diagrams were applied to identify the main causes of rejects and provide improvement solutions. The results showed that the biggest rejects were contaminated products (28%), followed by cracks (25%), leaks (21%), nonconforming contents (14%), and non-tight capshil (12%). The implementation of SPC helped improve production efficiency and product quality, and reduced the reject rate.